Inequality and Growth : Patterns and Policy, Volume 1. Concepts and Analysis - Basu, Kaushik (Palgrave Macmillan, 2016)
It was a part of the wisdom of mainstream economics that in the early stages of development inequality would rise but as growth persisted, it would, eventually, decline. Early evidence seemed to suggest that this pattern would be borne out. But, as time passed and growth persisted, inequality continued to grow, casting doubt on the received wisdom. The aim of this two-volume book is to analyze the current state of global and regional inequality, dissect the phenomenal increase in inequality that we have seen occur in recent times, and better understand the complex relationship between inequality and development. The political instability and conflict that we see around the world, arguably, has connection to economic deprivation of large segments of society and the perception of marginalization. This two-volume work acquires a special significance in the light of these developments.